Reliability of acridine orange fluorescence microscopy in oral cytodiagnosis - Nilima Prakash; P Sharada; G L Pradeep; N Soundarya (Wolters Kluwer Medknow Publications, 2011)
Context and Aims: The oral cavity is the most predominant location in the head and neck region for primary malignant epithelial tumors. Oral cancer is estimated to be the sixth most common malignancy. Early recognition is imperative for successful treatment and good prognosis. Exfoliative cytology is a simple and reasonably effective technique for rapid initial evaluation of a suspicious oral lesion. The present study was conducted to determine the reliability of acridine orange fluorescence microscopy for cytodiagnosis as a more rapid and easier method for the final evaluation of the cytological specimen. Materials and Methods: Smears were collected from 20 individuals with oral lesions suspicious of malignancy, oral lesions not suggestive of malignancy and normal buccal mucosa. One smear was stained with Papanicolaou stain and another one with acridine orange stain. The differences in the study group and control group were compared by means of the χ2 (Chi-square) test. The results were considered statistically significant whenever P was <0.05. Results: The acridine orange fluorescence stain reliably demonstrated malignant cells based on the differential fluorescence - a cytochemical criterion. The efficacy of the stain was higher than the conventional Papanicolaou stain in screening of oral lesions suspicious of malignancy. However, the acridine orange fluorescence stain did not differentiate effectively between malignant cells and rapidly proliferating cells, as the technique is based on the nucleic acid content. Conclusion: The fluorescent acridine orange method can be used reliably for the screening of carcinomas and it is especially helpful in the follow-up detection of recurrent carcinoma in previously treated cases.